Is there a relationship between birth quartile and vertical jump performance among young male elite volleyball athletes? - de Oliveira Castro, H.; Lima, R. F.; Savassi Figueiredo, L.; de Oliveira, V.; Peyre-Tartaruga, L. A.; Martins Kruel, L. F.; Iop Laporta, L.; De Conti Teixeira Costa, G.; Pereira Berriel, G. (Perceptual and Motor Skills, 2024)
Vertical jump is an important skill that influences volleyball performance. In this study, we analyzed the relationship between vertical jump performance and birth quartile of Brazilian male youth volleyball players. We calculated chi-square goodness-of-fit tests to compare the athletes` birthdate distributions in quarters of their birth years (Q1, Q2, Q3, and Q4) according to player age categories (U17, U18, U19, and U21). We calculated one-way ANOVAs to compare spike jump and block jump heights of players born in different quarters of the same year. Overall, we found a relative age effect (i.e., more players with birth dates early in the birth year) in U17 (p < .001), U18 (p < .001), U19 (p < .001), and U21 (p = .04). Regarding vertical jump performance, U18 athletes born in Q2 reached higher spike jump heights (p = .006) and block jump heights (p = .002) than athletes born in Q4, and U19 athletes born in Q1 reached higher block jump heights than athletes born in Q3 (p = .049). There were no significant differences in vertical jump performance across birth quartiles among U17 and U21 athletes. Thus, a relative age effect was present in all age categories but not always reflected in vertical jump performance. Volleyball coaches and policymakers are still advised to employ strategies to ensure fairer opportunities for players born later in the year of their eligibility dates, as we found RAE to be sometimes, but not always, related to higher spike or block jump heights even among these older adolescents and young adult athletes.